Interaksi Media Sosial dan Minat Baca di Kalangan Gen Z - Anhar, Anhar; Hazlin, Nur Azra Amanda; Simanjuntak, Adelia; Nurbidayah, Diandra (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to examine the interaction between social media and reading interest among Gen Z, a generation born in the digital era and highly dependent on social media in daily life. Using a qualitative descriptive approach, this study explores Gen Z's perception of the impact of social media on reading habits, both positively and negatively. The type of research used is a qualitative descriptive approach. Data was obtained from 20 informants through semi-structured interviews and observation of social media activities related to literacy. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawn. The results of the study show that although social media diverts some attention from conventional reading activities, this platform can also be used as a tool to promote literacy through online reading communities and literacy-related content. This research provides important insights for the development of strategies to increase reading interest among the younger generation.